The weight of the worlds - Cox, Greg, 1959- (Star trek, the original series., 2013)
When the remote colony of Ephrata is threatened by the alien Coven, Captain James T. Kirk and the crew of the U.S.S. Enterprise try to stop the Coven before they use dimension-crossing ships to take over the entire Federation.